Proposal of a new model of personal strategic alignment for human resources professionals in strategic positions - Costa, Denize Athayde Dutra da (2022)
Fil: Costa, Denize Athayde Dutra da. Instituto Desenvolvimento Empresarial. Fundação Getúlio Vargas; Brasil.